Film Promotion in the Digital Universe. The End of the Cinema Exhibition in Spain. - Deltell, Luis; García Fernández, Emilio C. (Historia y Comunicación Social, 2014)
This article is a research on the status of the promotion, distribution and exhibition in Spain. Tackling the new forms of promotion and exhibition and the new model of viewer/spectator/audience in the Digital Universe.
Keywords: Brand; Spanish Cinema; Internet